A guide to investing in collectively held resources - Gnych, Sophia; Lawry, Steven; Monterroso, Iliana; Adhikary, Anukram; McLain, Rebecca (Center for International Forestry Research, 2019)
Impact investors typically finance businesses that seek to challenge the status quo, valuing environmental and social outcomes to deliver more sustainable returns on investment. Microfinance institutions such as Grameen and FINCA lead the way in financing poor and marginalized groups. Now, however, increasing attention is being given to help investors respect land rights and form equitable partnerships with communities living in rural areas. Communities are increasingly being given rights to manage the world¹s remaining common pool resources (CPR) – such as forests, pastures and fisheries – as common property. As such, investors interested in accessing and developing these resources have the opportunity to work with a new investment partner, the community user group (CUG). This guide is designed to help investors better understand the challenges and opportunities of investing in resources managed collectively by a community – where the community is the principal investment partner! In this guide we draw on examples and lessons learned from four case-study countries considered to have the most successful arrangements for collectively managing natural resources. The case countries are Guatemala, Mexico and Nepal, which have devolved forest rights to communities, and Namibia, which has devolved wildlife rights.